William James : in the maelstrom of American modernism : a biography - Richardson, Robert D. (Boston : Houghton Mifflin, 2006)
Biographer Richardson has written a moving portrait of James--pivotal member of the Metaphysical Club and author of The Varieties of Religious Experience. The biography, ten years in the making, draws on unpublished letters, journals, and family records. Richardson paints extraordinary scenes from what James himself called the "buzzing blooming confusion" of his life, beginning with childhood, as he struggled to achieve amid the domestic chaos and intellectual brilliance of Father, brother Henry, and sister Alice. James was a beloved teacher who taught courage and risk-taking, and served as mentor to W.E.B. Du Bois, Gertrude Stein, and many other Harvard outsiders. Richardson also illuminates James's hugely influential works. One of the great figures in mysticism here brought richly to life, James is a man "whose leading ideas are still so fresh and challenging that they are not yet fully assimilated by the modern world they helped to bring about."--From publisher description.
Includes bibliographical references (p. 530-589) and index.
Keywords: James, William; Philosophers -- United States -- Biography